2015
DOI: 10.1007/s00394-015-0934-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of vitamin B6 inadequacy, induced by exposure to the anti-B6 factor 1-amino d-proline, on plasma lipophilic metabolites of rats: a metabolomics approach

Abstract: Changes in these metabolites revealed a potential defect in pathways linked with the biosynthesis and metabolism of bile acid components, N-acyl amino acids, analgesic androgens, anti-inflammatory and neuroprotective molecules. We also noted that the changes in these biomarkers can be alleviated by the application of adequate vitamin B6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Importantly, while it was observed that diet-induced pyridoxine deficiency in these experimental animals resulted in lower body weight gains and organ weights compared to the controls, this was not statistically significant. Nevertheless, this is similar to observations in other studies [ [20] , [21] , [22] , 24 , 26 , [53] , [54] , [55] ].…”
Section: Discussionsupporting
confidence: 93%
“…Importantly, while it was observed that diet-induced pyridoxine deficiency in these experimental animals resulted in lower body weight gains and organ weights compared to the controls, this was not statistically significant. Nevertheless, this is similar to observations in other studies [ [20] , [21] , [22] , 24 , 26 , [53] , [54] , [55] ].…”
Section: Discussionsupporting
confidence: 93%
“…All analytical work was carried out in duplicate by blinded laboratory personnel who are unaware of the case/control status of plasma samples so to reduce unintentional bias. The laboratory workflow and procedures employed have been previously published [ 23 , 24 ] and are summarized briefly below.…”
Section: Methodsmentioning
confidence: 99%
“…Extraction of low-molecular-weight (<1500 Da) metabolites in plasma samples was done by as previously described 10 . Briefly, a volume of 100 microliters of plasma was mixed with a volume of 200 microliters of acetonitrile.…”
Section: Methodsmentioning
confidence: 99%